2019
DOI: 10.1002/jmri.26773
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous phase‐contrast MRI and PET for noninvasive quantification of cerebral blood flow and reactivity in healthy subjects and patients with cerebrovascular disease

Abstract: Background: H 2 15 O-positron emission tomography (PET) is considered the reference standard for absolute cerebral blood flow (CBF). However, this technique requires an arterial input function measured through continuous sampling of arterial blood, which is invasive and has limitations with tracer delay and dispersion. Purpose: To demonstrate a new noninvasive method to quantify absolute CBF with a PET/MRI hybrid scanner. This blood-free approach, called PC-PET, takes the spatial CBF distribution from a static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 39 publications
5
27
0
1
Order By: Relevance
“…Furthermore, global OEF MRI measurements from the superior sagittal sinus are more widespread and have been compared to each other with some success ( Barhoum et al, 2015 ). Whole-brain OEF information from MRI could thus be used as a scaling factor ( Ishii et al, 2020 ) for simultaneous [ 15 O]-oxygen PET/MRI studies and eliminate the need for invasive arterial blood sampling. Initial simulations suggest that global scaling of PET images with MRI-derived flow and whole-brain CMRO 2 measures is robust to signal variations related to recirculating water and CBV ( Narciso et al, 2019 ).…”
Section: Comparison With Mri and Opportunities With Simultaneous Pet/mentioning
confidence: 99%
“…Furthermore, global OEF MRI measurements from the superior sagittal sinus are more widespread and have been compared to each other with some success ( Barhoum et al, 2015 ). Whole-brain OEF information from MRI could thus be used as a scaling factor ( Ishii et al, 2020 ) for simultaneous [ 15 O]-oxygen PET/MRI studies and eliminate the need for invasive arterial blood sampling. Initial simulations suggest that global scaling of PET images with MRI-derived flow and whole-brain CMRO 2 measures is robust to signal variations related to recirculating water and CBV ( Narciso et al, 2019 ).…”
Section: Comparison With Mri and Opportunities With Simultaneous Pet/mentioning
confidence: 99%
“…In contrast, previous studies using 15 O-water PET with arterial sampling have reported CBF values in GM ranging from 37 to 67 mL/100 g/min in healthy subjects [ 11 , 28 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Thus, current published normal-range CBF measured by 15 O-water PET with arterial blood sampling shows large variations [ 36 , 42 ]. A generally accepted and often-cited average normal whole-brain CBF value in younger adults is 50 mL/100 g/min [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…the whole brain flow measured by phase-contrast imaging. 47,48 However, scaling methods should be used cautiously, as systematic bias has been shown between phase-contrast MRI and 15 O-water PET with arterial sampling, 43,49 especially at lower spatial resolutions and for higher flow rates. Furthermore, the validity of phase-contrast MRI in patients with steno-occlusive disorders is less well understood.…”
Section: Discussionmentioning
confidence: 99%